THE LAW ENFORCEMENT OF NARCOTICS CRIME: A Case Study of District Court Decision No. 936/PID.SUS/2021/PN.SDA - Udin, M. Bachrul Ulum; Widoyoko, Wreda Danang (jfpublisher, 2022)
This research contained the forms of criminal responsibility in the narcotics crime based on a case study of district court No. 936/PID.SUS/2021/PN.SDA and its aim to find out the judge's consideration against the criminal act of storing narcotics in class 1 for cannabis type. The research was conducted in Sidoarjo District Court by analyzing the judge who handled the case related to the narcotics crime and examining documents related to the existing case. There are two important things which described the problem solving of this case, these are (1) criminal responsibility in narcotics crimes fulfills the elements of criminal responsibility, such as being able to take responsibility, the existence of intentional mistakes and no leniency for the accused in order to held accountable; (2) the judge's legal considerations in deciding the decision on the criminal case No. 936/PID.SUS/2021/PN.SDA with the existence of valid evidence and the judge is sure of its evidence.